Perception of Correctly and Incorrectly Produced Words in Children With and Without Phonological Speech Sound Disorders. - Brosseau-Lapré, Françoise; Schumaker, Jennifer (Journal of Speech, Language & Hearing Research, 2020)
Purpose: The purpose of this study was to examine the perception of correctly and incorrectly produced words in children with and without phonological speech sound disorder (SSD) with similar vocabulary and language skills. Method: Thirty-six monolingual English-speaking children aged 4 and 5 years, half with SSD and half with typical speech and language skills, participated in this study. Participants completed standardized speech and language tests as well as a mispronunciation detection task targeting omissions and substitutions of the phonemes /k, s, .../ in five word positions/shapes. Results: The children with SSD obtained significantly lower perceptual accuracy than the children with typical development. There was no statistically significant effect for phoneme. Omissions were more likely to be detected by both groups of participants compared with substitutions, and children with SSD had greater difficulty identifying substitutions as incorrectly produced words. Conclusions: Speech perception difficulties may be a distinguishing feature of children with phonological SSD and without concomitant language difficulties. Further research is needed to investigate specific speech contexts in which perception predicts accurate production in children with SSD.